The drafter - Harrison, Kim, 1966- (Harrison, Kim, 1966- Peri Reed chronicles., 2015)
"Detroit 2030: Double-crossed by the person she loved and betrayed by the covert government organization that trained her to use her body as a weapon, Peri Reed is a renegade on the run. Don't forgive and never forget has always been Peri's creed. But her day job makes it difficult: she is a drafter, possessed of a rare, invaluable skill for altering time, yet destined to forget both the history she changed and the history she rewrote. When Peri discovers her name is on a list of corrupt operatives, she realizes that her own life has been manipulated by the agency. Her memory of the previous three years erased, she joins forces with a mysterious rogue soldier in a deadly race to piece together the truth about her fateful final task. With only her intuition to guide her, she's on a vengeful mission to decide-who must she kill and who, including herself, can she trust?